Peroxisome Proliferator-Activated Receptor β/δ in the Brain: Facts and Hypothesis - M. G. Hall; Laure Quignodon; Béatrice Desvergne (PPAR Research)
peroxisome proliferator-activated receptors (PPARs) are nuclear receptors acting as lipid sensors. Besides its metabolic activity in peripheral organs, the PPAR beta/delta isotype is highly expressed in the brain and its deletion in mice induces a brain developmental defect. Nevertheless, exploration of PPARβ action in the central nervous system remains sketchy. The lipid content alteration observed in PPARβ null brains and the positive action of PPARβ agonists on oligodendrocyte differentiation, a process characterized by lipid accumulation, suggest that PPARβ acts on the fatty acids and/or cholesterol metabolisms in the brain. PPARβ could also regulate central inflammation and antioxidant mechanisms in the damaged brain. Even if not fully understood, the neuroprotective effect of PPARβ agonists highlights their potential benefit to treat various acute or chronic neurological disorders. In this perspective, we need to better understand the basic function of PPARβ in the brain. This review proposes different leads for future researches.